2016
DOI: 10.1159/000444084
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Cognitive Stimulation and Physical Exercise Programme (MINDVital) in Early Dementia: Differential Effects on Single- and Dual-Task Gait Performance

Abstract: Background: Gait disorders are common in early dementia, with particularly pronounced dual-task deficits, contributing to the increased fall risk and mobility decline associated with cognitive impairment. Objective: This study examines the effects of a combined cognitive stimulation and physical exercise programme (MINDVital) on gait performance under single- and dual-task conditions in older adults with mild dementia. Methods: Thirty-nine patients with early dementia participated in a multi-disciplinary rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
(41 reference statements)
1
35
0
1
Order By: Relevance
“…In contrast to previous studies, which predominantly reported positive effects for stride length and stride time in single and dual task conditions [ 39 – 46 ], our investigation did not confirm the effectiveness of an MEP for these spatiotemporal gait parameters. In accordance with 20 previous studies, we did not observe statistically significant effects on walking speed [ 24 38 , 42 , 44 , 47 , 48 ] and percent of double support [ 44 , 45 ], while twelve others did for single [ 17 23 , 40 , 41 , 43 , 46 ] and dual task conditions [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to previous studies, which predominantly reported positive effects for stride length and stride time in single and dual task conditions [ 39 – 46 ], our investigation did not confirm the effectiveness of an MEP for these spatiotemporal gait parameters. In accordance with 20 previous studies, we did not observe statistically significant effects on walking speed [ 24 38 , 42 , 44 , 47 , 48 ] and percent of double support [ 44 , 45 ], while twelve others did for single [ 17 23 , 40 , 41 , 43 , 46 ] and dual task conditions [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most previous studies conducted multimodal physical activity interventions, including strength, balance, and aerobic exercises [ 17 21 , 23 25 , 28 , 30 – 36 , 39 – 45 , 47 ]. Given the relationship between motor, cognitive and gait performance, as well as the positive impacts of cognitive training programs [ 1 , 11 ], interventions combining physical and cognitive activity may be most promising for improving gait performance in IWD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is about collaborative engagement -co-ownership throughout the process. Another paper by Tay et al (2016) went into more depth about their goal-oriented approach (Chew, Chong, Fong, & Tay, 2015). Cognition goals as well as goals to improve engagement and socialization; reduce caregiver stress; and improve physical function, behaviour and mood were set and 61.8% of participants met them.…”
mentioning
confidence: 99%
“…Gait-cognition dual-task paradigms have demonstrated that dual-task interference is more pronounced in older compared to younger adults [10] and in those with neurological disorders including stroke [11], Parkinson’s disease [12], and AD [13]. Gait interference during dual-tasking is associated with risk of falls [14, 15] and is increasingly incorporated as an outcome in rehabilitation research [16, 17].…”
Section: Introductionmentioning
confidence: 99%